Study of the chemical composition of argan oil according to the shape of the fruit - M. Hilali; L. El Hammari; H. El Monfalouti; N. Maata; B. E. Kartah (Труды по прикладной ботанике, генетике и селекции)
The aim of this study was to investigate the effect of phenotypic diversity of argan fruit with different morphological characteristics (fusiform, oval, apiculate and spherical) on fat and protein content, inflexibility and fat chemical composition, oil acids and sterols. To investigate the links of argan fruit shape with the chemical composition of argan oil, with the help of native communities, 4 different fruit shapes (fusiform, apiculate, spherical and oval) were selected, which were harvested from the same place (Tamanar) in Essaouira province (South Plain region, Western Morocco). After harvesting the fruit of the argan tree, 100 samples were taken from each form. They were crushed to destroy the core. After extraction of hexane with Soxhlet, fat content, protein level, unsaponifiable content, composition of fatty acids and sterols in fat were determined. The results showed that the oval shape is the best shape of argan fruit because their kernels contain more than 50% fat and a higher percentage of unsaponifiables. The results on fatty acids and sterols showed that argan oil contained 80% of unsaturated fatty acids. The results also showed that the main products of the sterol composition in argan oil were schottenol (or Δ-7-stigmasterol) (42.8 and 46.4%) and spinasterol (39.8 and 45.6%). The study of the chemical composition showed that there was no correlation between the shape of the fruit of the argan tree and the composition of fatty acids. Depending on the shape of the argan fruit, fatty acids and sterols were not only related to the shape but also to the nature of the soil and its altitude, longitude and distance from the sea.